2020
DOI: 10.1270/jsbbs.20027
|View full text |Cite
|
Sign up to set email alerts
|

Development of diagnostic molecular markers for marker-assisted breeding against bacterial wilt in tomato

Abstract: Bacterial wilt, caused by the Ralstonia pseudosolanacearum species complex, is an important vascular disease that limits tomato production in tropical and subtropical regions. Two major quantitative trait loci (QTL) of bacterial wilt resistance on chromosome 6 ( Bwr-6 ) and 12 ( Bwr-12 ) were previously identified in Solanum lycopersicum ‘Hawaii 7996’; however, marker-assisted breeding for bacterial wilt resistance is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…From this study, genotypes LA 0442, LA 2443, LA 0376 and H7996 recorded the lowest levels of incidence and severity of the BW disease throughout the study. The variation in the level of BW incidence and severity among the tomato genotypes observed in this study could be due to the differences in their genetic makeup as reported by [30] who screened 27 cultivars for resistance to bacterial wilt disease and identified resistant genotypes with low mean disease severity scores in several genotypes including Hawaii 7996, BWR-20, Spider, High Power, IT 201664, Hawaii 7998, and Fighting. Comparing the resistance level using the susceptible check Petofake as a reference, H7996, LA 0442 and LA 0443 were of higher resistance to BW disease followed by LA 0376, AVTO 1717 and LA 2701.…”
Section: Discussionmentioning
confidence: 51%
“…From this study, genotypes LA 0442, LA 2443, LA 0376 and H7996 recorded the lowest levels of incidence and severity of the BW disease throughout the study. The variation in the level of BW incidence and severity among the tomato genotypes observed in this study could be due to the differences in their genetic makeup as reported by [30] who screened 27 cultivars for resistance to bacterial wilt disease and identified resistant genotypes with low mean disease severity scores in several genotypes including Hawaii 7996, BWR-20, Spider, High Power, IT 201664, Hawaii 7998, and Fighting. Comparing the resistance level using the susceptible check Petofake as a reference, H7996, LA 0442 and LA 0443 were of higher resistance to BW disease followed by LA 0376, AVTO 1717 and LA 2701.…”
Section: Discussionmentioning
confidence: 51%
“…Forty-seven tomato cultivars were evaluated for bacterial canker resistance including previously reported cultivars such as resistant “IRAT L-3” ( Stüwe and von Tiedemann, 2013 ) and susceptible “Moneymaker” ( Mohd Nadzir et al, 2019 ). For the qualitative resistance screening, cultivars were classified as resistant (disease severity score ≤ 2.0) and susceptible (disease severity score ≥ 3.0; Bartkiewicz et al, 2018 ; Abebe et al, 2020 ). Accordingly, 11 cultivars were grouped as resistant and 36 as susceptible ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Diagnostic markers are molecular markers that are significantly linked with one or more traits, which help in the early and rapid identification of a target phenotype ( Chakdar et al., 2019 ). Diagnostic markers have been successfully employed in many traits of various plants, such as the rust resistance trait in wheat ( Liu et al., 2021 ) and common wheat ( Wu et al., 2018 ), the testa color in cultivated peanut ( Chen et al., 2021 ), and the bacterial wilt trait in tomato ( Abebe et al., 2020 ). In the present study, three Indel markers located in the PH1.1 region were validated to be closely linked with the plant height of broomcorn millet using a total of 512 accessions.…”
Section: Discussionmentioning
confidence: 99%